Perlindungan dan Penegakan Hukum bagi Pengemudi Transportasi Online dalam Perspektif Hubungan Hukum dengan Aplikator di Indonesia - Adjie Akbar; M.S Tumanggor; Adi Nur Rohman (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
This study aims to identify the most appropriate form of legal protection for online drivers. It adopts a normative legal research approach (c), focusing on the application of law and conceptual frameworks, particularly in relation to partnership agreements. This research does not involve hypothesis testing, as normative legal research does not employ hypotheses or empirical data, but rather relies on legal materials.The findings reveal fundamental differences between partnership agreements and employment contracts. The partnership relationship between online drivers and application service providers is unique, as both parties are formally considered equal under Article 36 of Law Number 20 of 2008. However, in social and economic practice, online drivers are often in a weaker position. Therefore, the government, as the sovereign authority, should intervene by providing legal protection through legislation and public policy. Such protection is essential to uphold the rights of online drivers and aligns with John Rawls’ theory of distributive justice